Updates in Intraductal Papillary Mucinous Neoplasm Clinical Risk Stratification - Bingmer, Katherine; Burkhart, Richard A. (Digestive Disease Interventions, 2025)
Pancreatic intraductal papillary mucinous neoplasms (IPMNs) comprise a majority of pancreatic cystic neoplasms and are precursors of pancreatic ductal adenocarcinoma. Ideal management involves surgical resection of IPMN that harbors high-grade dysplasia prior to the development of invasive disease in appropriate patients. Additionally, identification of low-risk IPMN allows for avoidance of unnecessary morbidity associated with surgical resection. Malignant potential varies widely and it can be difficult to predict which IPMNs are at highest risk. A number of studies and guidelines have been published to assist clinicians in stratification of IPMNs into those that should be considered for surgical resection, those which warrant close surveillance, and those in whom you may safely consider cessation of surveillance. This review will summarize recent literature that can help guide the clinical management of IPMN based on malignant potential.
Keywords: intraductal papillary mucinous neoplasm; pancreatic ductal adenocarcinoma; guidelines